PROTECTIVE EFFECT OF QUERCETIN ON THE ORAL CAVITY TISSUES IN RATS IN THE PRESENCE OF GENOTOXICANT AND ALIMENTARY DEFICIENCY OF POLYPHENOLS - Borodach, V.A.; Schnaider, S.A.; Suslova, O.V.; Savieliieva, N.N.; Anisimova, L.V.; Tkachenko, Ye.K. (World of Medicine and Biology, 2020)
The purpose of the study was to establish the effect of the flavonoid quercetin on the oral cavity tissues in rats in the presence of genotoxicant fluorouracil with insufficient intake of plant polyphenols. The experiment was carried out on 21 white rats of the Wistar line. Intact animals were kept on a standard vivarium diet. The control group received a 5% fluorouracil solution per os against the background of a flavonoid diet; freshly prepared 7.5% potato starch gel was applied to the oral mucosa of the rats. Group 3 rats were additionally treated daily with a gel containing quercetin at a dose of 0.25 mg/kg. The experiment lasted 70 days. The gums turned out to be more sensitive than the buccal mucosa to long-term exposure to the genotoxicant fluorouracil in the case of nutritional deficiency of plant polyphenols. Quercetin in the accepted experimental conditions showed a significant anti-inflammatory effect in the buccal mucosa.
Keywords: fluorouracil; nutritional deficiency of plant polyphenols; quercetin; gums; buccal mucosa; protective effect; rats